The role of religiosity to address the mental health crisis of students: a study on three parameters (anxiety, depression, and stress) - Misran, Rohmah Najihah; Abdul Khaiyom, Jamilah Hanum; Razali, Zul Azlin (UPM Press, 2021)
Religiosity is a construct that has interesting implications in the mental health issues of youths. This study examines the role of religiosity on anxiety, depression, and stress using 148 Muslim students studying Islamic studies at undergraduate provision in an Islamic University as sample. Results indicated that the level of religiosity among the participants ranged from moderately religious to highly religious. The mean levels of anxiety, depression, and stress among the participants were moderate, and a significant number of students suffered from severe psychological distress. Female students were reported to experience significantly slightly more stress than male students. Furthermore, the relationship between religiosity, anxiety, and depression was significantly negative but not stressful. Further analysis found that religiosity serves as a protective factor for depression. Meanwhile, some religiosity components (i.e., avoidance of sinful acts and frequent conduct of recommended acts) were found to be a significant protective factor against anxiety and depression, respectively. Thus, in retrospect, mental health and religion appear to converge on managing psychological distress. As so to speak, this is a vital point in the emerging mental health services in which the incorporation of religious components into clinical practice may show good promising results in aiding the recovery process of psychological health issues. Likewise, embedding religiosity in one’s life, or being religiously minded, reflected in daily life manifestation, is linked with better mental health outcomes.